Acute Acalculous Cholecystitis with Empyema due to Salmonellosis - Georgios D. Lianos; Panagiota Drosou; Rizos Souvatzoglou; Anastasia Karampa; Georgios Vangelis; Emmanouil Angelakis; Vassilios Pappas; Epameinontas Lekkas (Case Reports in Gastrointestinal Medicine)
Empyema of acalculous gallbladder in the setting of salmonellosis represents an extremely rare and life-threatening clinical condition in adults. In this unique case report, we deal with a previously healthy patient who developed acalculous cholecystitis and empyema due to infection by Salmonella. He underwent explorative laparotomy in emergency setting, and cholecystectomy was performed due to his toxic clinical condition. Empyema of gallbladder was revealed and cultures were collected. A combination of antibiotics (ciprofloxacin and metronidazole) was set, and the patient was discharged 8 days after the surgical operation in good condition. It has to be highlighted that acalculous cholecystitis is a rare entity, mostly at critically ill patients, and treatment options depend on clinical condition, risk factors, and etiology. To our knowledge, this is the first case report dealing with acalculous cholecystitis with empyema due to salmonellosis up to date. Although it is extremely rare, high index of suspicion is needed by the operating surgeon in order to avoid unfavorable outcomes.